2018
DOI: 10.16986/huje.2018038807
|View full text |Cite
|
Sign up to set email alerts
|

Doing English-Only Instructions: A Multimodal Account of Bilingual Bangladeshi Classrooms

Abstract: ABSTRACT:The research reported here is part of a broader research project on bilingual Bangladeshi ESL schools. The study seeks to find out how a prescribed language policy that is operating at the school informs classroom instruction. To do so, it uses the distinction between medium of instruction and medium of interaction, introduced by Bonacina & Gafaranga (2011), to examine how participants to instructional exchanges orient their actions to the language policy as well as to locally emerging interactional c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
1
1
1
Order By: Relevance
“…In line with findings from other studies of HL settings as well as other types of language classrooms (Amir, 2013;Creese et al, 2011;Huq, 2018;Li Wei & Wu, 2009;Musk, 2006Musk, , 2010Slotte-Lüttge, 2005), the present thesis has shown that a monolingual norm was in place in the data and that this norm was co-constructed in and through the interaction that took place in the classroom. However, in contrast to findings from foreign language classrooms, where the English-only rule was imposed from 'above' i.e.…”
Section: Social Interaction In the Language Classroomsupporting
confidence: 90%
See 2 more Smart Citations
“…In line with findings from other studies of HL settings as well as other types of language classrooms (Amir, 2013;Creese et al, 2011;Huq, 2018;Li Wei & Wu, 2009;Musk, 2006Musk, , 2010Slotte-Lüttge, 2005), the present thesis has shown that a monolingual norm was in place in the data and that this norm was co-constructed in and through the interaction that took place in the classroom. However, in contrast to findings from foreign language classrooms, where the English-only rule was imposed from 'above' i.e.…”
Section: Social Interaction In the Language Classroomsupporting
confidence: 90%
“…However, in contrast to findings from foreign language classrooms, where the English-only rule was imposed from 'above' i.e. via the school's or teacher's explicit policy (Amir, 2013;Huq, 2018), in my data the norm was constructed in a somewhat more implicit manner. Paradoxically, it is precisely in the teacher's distinct and structured inclusion of Swedish lexical items that constructs Swedish as the dispreferred language.…”
Section: Social Interaction In the Language Classroomcontrasting
confidence: 64%
See 1 more Smart Citation